Effect of solution treatment temperature on microstructure and mechanical properties of hot isostatically pressed superalloy Inconel* 718 - Rao G.A.; Srinivas M.; Sarma D.S. (My University, 2025)
Hot isostatically pressed superalloy Inconel 718 heat treated as per the standard schedule of aerospace material specification (AMS) 5662 (solution treatment at 980°C/1 h/water quenching followed by two step aging at 720°C/8 h/ furnace cooling to 620°C/8 h/air cooling to room temperature) has shown yield strength (YS) and ultimate tensile strength (UTS) comparable to that of wrought heat treated alloy, but it had poor ductility and inferior stress rupture properties. To find an appropriate heat treatment to improve these properties, the influence of solution treatment temperature on the structure and properties of the alloy has been studied. The results show that although YS and UTS decrease with increasing solution treatment temperature, considerable improvement occurs in the ductility of the unaged alloy. For the aged alloy, an increase in solution treatment temperature resulted in only a marginal improvement in strength, but the 650°C ductility and stress rupture life were improved significantly. This has been attributed to the dissolution of MC carbides and disruption of prior particle boundaries (PPBs) at higher solution treatment temperatures that had led to enhanced bonding between the particles. Fractography studies revealed a transgranular ductile mode of fracture for the unaged condition for all solution treatment temperatures. In contrast, aged alloys subjected to lower solution treatment temperatures have shown decohesion of particle boundaries leading to an intergranular mode of fracture, while alloys solution treated at temperatures greater than 1250°C revealed a transgranular ductile mode of fracture suggestive of improved ductility. The improvement of high temperature properties obtained by higher solution treatment temperature makes it possible to explore the near net shape capability of IIIP technology to its maximum potential, when adopted for producing alloy 718 components.